OKUPANSI TANAH DALAM KAWASAN HUTAN YANG DIKELOLA PERUM PERHUTANI DIVRE JAWA TIMUR - Nurcahyo, Hanif (Jurnal Cakrawala Hukum, 2016)
Occupation by the Magersari community for settlements raises tenure or land disputes within forest areas. The settlement of land rights disputes by the Magersari community for settlement to Perum Perhutani East Java Regional Division is pursued by the Swap of Forest Area Exchanges. The purpose of this study is to find the legal implications of regulation on the mechanism of a land swap in the forest area and to find the constraining factor faced by Perum Perhutani East Java Regional Division in the process of land exchange within the forest area. The research approach is conducted by normative juridical. Subsequently classified and grouped the legal material and analyzed by qualitative juridical. The results of this study that the mechanism of exchange of state forest land for non-forestry interests many obstacles faced by the â€œmagersariâ€ community and Perum Perhutani.Hard difficult to find a replacement land adjacent to the forest. Birocracy permissions that make it difficult and takes a long time. Coordination between related institutions less resulting in overlapping authority.